Leonard Porter Ayres papers - Ayres, Leonard Porter, 1879-1946.; Young, Agnes Brooks, 1898-1974.
Correspondence, memoranda, journals, reports, notes, subject files, printed matter, statistical tables and graphs, clippings, and other papers relating chiefly to Ayres's career as a statistician, military officer, and educator. Documents his service as chief statistical officer for the U.S. War Dept. during World War I, technical adviser to the Allied Powers Reparation Commission as part of the Dawes Committee in 1924, consultant to the War Dept. between the wars, and statistical coordinator for the War Dept. and consultant to the U.S. War Manpower Commission during World War II. Also documents his years as an educator in Puerto Rico, 1902-1908; his work with the Cleveland Foundation Survey Committee, Cleveland Trust Company, and Russell Sage Foundation; and his travels in Europe. Subjects include education, especially in Puerto Rico and Cleveland, Ohio; and the American colonial administration and life in Puerto Rico. Includes a journal kept by Agnes Brooks Young as Ayres's secretary at the War Dept. and War Manpower Commission, a file of correspondence between Christian Herter and Alan Goldsmith relating to the Dawes Committee, and Ayres family correspondence.
Library of Congress Prints and Photographs Division.
Statistician, economist, educator, and army officer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room.
Keywords: Goldsmith, Alan Gustavus, -- 1892-1961 -- Correspondence; Herter, Christian Archibald, -- 1895-1966 -- Correspondence; United States. -- War Department; United States. -- War Manpower Commission; Allied Powers (1919- ). -- Reparation Commission; Cleveland Foundation. -- Survey Committee; Cleveland Trust Company; Russell Sage Foundation; Education; Education -- Ohio -- Cleveland; Education -- Puerto Rico; World War, 1914-1918 -- Reparations; World War, 1914-1918 -- Statistics; World War, 1939-1945 -- Statistics; Europe -- Description and travel; Puerto Rico -- History -- 20th century; Puerto Rico -- Social life and customs; Ayres family -- Correspondence; Army officers; Economists; Educators; Statisticians